2007
DOI: 10.1152/ajpheart.01339.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acetylcholinesterase inhibition with pyridostigmine on cardiac parasympathetic function in sedentary adults and trained athletes

Abstract: Dewland TA, Androne AS, Lee FA, Lampert RJ, Katz SD. Effect of acetylcholinesterase inhibition with pyridostigmine on cardiac parasympathetic function in sedentary adults and trained athletes. Am J Physiol Heart Circ Physiol 293: H86-H92, 2007. First published February 23, 2007 doi:10.1152/ajpheart.01339.2006.-Heart rate variability and postexercise heart rate recovery are used to assess cardiac parasympathetic tone in human studies, but in some cases these indexes appear to yield discordant information. We ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
65
1
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 58 publications
11
65
1
7
Order By: Relevance
“…Cholinergic status values improved pulse predictions even when controlled for all other risk factors in men but not in women (24), compatible with the antiinflammatory effect of cholinergic signaling (14) as well as with previous reports of protective acetylcholine effects on ischemic myocardium (26), and with the pulse improvement effects of the AChE inhibitor pyridostigmine (27).…”
Section: Significancesupporting
confidence: 86%
“…Cholinergic status values improved pulse predictions even when controlled for all other risk factors in men but not in women (24), compatible with the antiinflammatory effect of cholinergic signaling (14) as well as with previous reports of protective acetylcholine effects on ischemic myocardium (26), and with the pulse improvement effects of the AChE inhibitor pyridostigmine (27).…”
Section: Significancesupporting
confidence: 86%
“…Dewland, Androne, Lee, Lampert, and Katz (2007) found no relationship between resting HRV and HRR from maximal exercise.…”
Section: Relationship Of Heart Rate Variability To Heart Rate Recoverymentioning
confidence: 91%
“…Dewland et al utilized the acetylcholinesterase inhibitor pyridostigmine to augment parasympathetic signaling at the sinoatrial node in ten sedentary subjects (mean age 37 ± 7 years, mean VO 2max 29.4 ± 6.2 ml/kg per min) and ten endurance-trained athletes (mean age 27 ± 8 years, mean VO 2max 53.3 ± 11.3 ml/kg per min). These investigators demonstrated that pyridostigmine increased HRR in sedentary subjects, but not in trained athletes, and did not alter HRV in either group [7].…”
mentioning
confidence: 92%
“…Dewland et al utilized the acetylcholinesterase inhibitor pyridostigmine to augment parasympathetic signaling at the sinoatrial node in ten sedentary subjects (mean age 37 ± 7 years, mean VO 2max 29.4 ± 6.2 ml/kg per min) and ten endurance-trained athletes (mean age 27 ± 8 years, mean VO 2max 53.3 ± 11.3 ml/kg per min). These investigators demonstrated that pyridostigmine increased HRR in sedentary subjects, but not in trained athletes, and did not alter HRV in either group [7].In this issue, Esco et al [8] report the findings of a crosssectional study that further supports the viewpoint that HRV and HRR are independent measures of parasympathetic function. The investigators recruited a sample of 66 healthy subjects (mean age 22.74 ± 3.64 years, mean VO 2max 46.39 ± 8.23 ml/kg per min) and demonstrated no association between any time domain or frequency-domain measure of HRV and HRR in this population.…”
mentioning
confidence: 94%
See 1 more Smart Citation